2014
DOI: 10.1155/2014/248960
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Estimation of Paracetamol, Ambroxol Hydrochloride, Levocetirizine Dihydrochloride, and Phenylephrine Hydrochloride in Combined Tablet Formulation by First-Order Derivative Spectrophotometry

Abstract: Paracetamol, ambroxol hydrochloride, levocetirizine dihydrochloride, and phenylephrine hydrochloride are used in combination for the treatment of chronic sinusitis, rhinitis, fever, nasal discharge, sore throat, and wheezing. The present work deals with method development for simultaneous estimation of paracetamol, ambroxol hydrochloride, levocetirizine dihydrochloride, and phenylephrine hydrochloride in tablet formulation by first-order derivative spectrosphotometry. For determination of sampling wavelength, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Phenylephrine decreases the congestion and the production of mucus thereby reducing discomfort and making breathing easier . To date, just a few methods have been introduced in the literature for the determination of phenylephrine, most of which are spectrophotometric or chromatographic methods and electroanalytical techniques have been rarely reported …”
Section: Introductionmentioning
confidence: 99%
“…Phenylephrine decreases the congestion and the production of mucus thereby reducing discomfort and making breathing easier . To date, just a few methods have been introduced in the literature for the determination of phenylephrine, most of which are spectrophotometric or chromatographic methods and electroanalytical techniques have been rarely reported …”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that there are so many methods of analysis were reported for individual analysis of Levocetirizine Dihydrochloride, Phenylephrine hydrochloride, and Paracetamol, as well as with combination with other drugs [7][8][9][10][11][12][13][14][15][16][17][18][19] , but no method is reported for Simultaneous determination of Levocetirizine Dihydrochloride, Phenylephrine hydrochloride and Paracetamol in combination formulations. A proposed analytical method has been developed and validated as per ICH guideline 20 .…”
Section: Fig 1: Levocetirizine Fig 2: Phenylephrine Fig 3: Paracetmentioning
confidence: 99%
“…Determination of Paracetamol has been performed using various methods like reversed-phase high performance liquid chromatographic (RP-HPLC) with caffeine [1], in Pharmaceutical Mixture Using HPLC and GC-MS [15], by first-order derivative spectrophotometery in combination with ambroxol hydrochloride, levocetirizine dihydrochloride, and phenylephrine hydrochloride [16]. By RP-HPLC in combination with Chlorzoxazone, and Nimesulide [17].…”
Section: Tramadol -Hcl (±Cis-2-[(dimethyl Amino) Methyl]-1-(m-mentioning
confidence: 99%